PEMODELAN LAJU INFLASI DENGAN MENGGUNAKAN REGRESI NON-LINEAR BERBASIS ALGORITMA GENETIKA (Kasus: Kota-Kota di Pulau Jawa) - Wildan Mujahid; Muhammad Arif Tiro; Ruliana Ruliana (Program Studi Statistika Fakultas MIPA UNM, 2022)
This research is applied research that uses non-linear regression on the inflation rate data and the factors that are thought to influence it. By using the RESET Test, statistics are obtained, namely the RESET value = 3.7506 with P value = 0.04138, which means that the inflation data is appropriate to use non-linear regression. From the results of this study, it was found that the average inflation rate of 26 cities in Java was 22.08% with a standard deviation of 24.33%. From the results of this study it was also found that the consumer price index (X1), city/district minimum wages (X2), and regional gross domestic product (X3) are factors that affect the inflation rate with the best model with an RMSE value of 0.445.